Tarybinės vaikų poezijos specifikos klausimu - Linkevičius, Jonas (Literatūra, 1967)
The specific character of the Soviet children's poetry is not sufficiently examined by the science of Soviet literature. This article tries to reveal the main features of the Soviet children's poetry in their reciprocal bonds. While analysing the individual peculiarities of children's poetry, the specific character of the reader's age is shown as an objective factor of narration, composition and form. The article analyses the main features of a lyrical character, poetical language, dynamics, lyricism, folk-loreness. It emphasizes that the given peculiarities of Soviet children's poetry can't be understood according to standards and accepted at any rate that the work of literature may be valuable for its precise selection and co-ordination of stylistic means.